A Comparison of Fine-needle Aspiration, Core Biopsy, and Surgical Biopsy in the Diagnosis of Extremity Soft Tissue Masses - Kasraeian, Sina (Springer-Verlag, 2010)
BACKGROUND: Biopsy tissue can be obtained through a fine needle, a wider coring needle, or through an open surgical incision. Though much literature exists regarding the diagnostic yield of these techniques individually, none compare accuracy of diagnosis in the same mass. QUESTIONS/PURPOSES: We asked how the diagnostic accuracy of fine-needle aspiration, core biopsy, and open surgical biopsy compare in regard to identifying malignancy, establishing the exact diagnosis, and guiding the appropriate treatment of soft tissue masses. PATIENTS AND METHODS: We prospectively studied 57 patients with palpable extremity soft tissue masses, performing fine-needle aspiration, followed by core biopsy, followed by surgical biopsy of the same mass. RESULTS: Open surgical biopsy was 100% accurate on all accounts. With regard to determining malignancy, fine-needle aspiration and core biopsy had 79.17% and 79.2% sensitivity, 72.7% and 81.8% specificity, 67.9% and 76% positive predictive value, 82.8% and 84.4% negative predictive value, and an overall accuracy of 75.4% and 80.7%, respectively. In regard to determining exact diagnosis, fine-needle aspiration had a 33.3% accuracy and core biopsy had a 45.6% accuracy. With regard to eventual treatment, fine-needle aspiration was 38.6% accurate and core biopsy was 49.1% accurate. CONCLUSIONS: In soft tissue mass diagnosis, core biopsy is more accurate than fine-needle aspiration on all accounts, and open biopsy is more accurate than both in determining malignancy, establishing the exact diagnosis, and the guiding appropriate treatment. LEVEL OF EVIDENCE: Level I, diagnostic study. See Guidelines for Authors for a complete description of levels of evidence.